1980
DOI: 10.1063/1.328396
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of narrow stripe InGaAsP/InP buried heterostructure lasers

Abstract: InGaAsP/InP buried-heterostructure lasers with a stripe width of 1–2 μm have been fabricated by two-step liquid phase epitaxy and preferential chemical etching. They operate in the fundamental transverse mode at wavelengths of ∼1.3 μm with threshold current as low as 22 mA. The temperature limit for cw operation is 80 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The Buried-Heterostructure (BH), InGaAsP, 1.3-/im laser* consid ered for use in the optical submarine cable system is the product of a new technology. 1 ' 3 Hence, the primary objective of this prequalification program is to make a preliminary determination of the extent to which the reliability of this 1.3-μπι laser satisfies the stringent require ments of the submarine cable system. The program concentrates on the projection of 1.3-^m laser performance to 10°C, which is the system operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The Buried-Heterostructure (BH), InGaAsP, 1.3-/im laser* consid ered for use in the optical submarine cable system is the product of a new technology. 1 ' 3 Hence, the primary objective of this prequalification program is to make a preliminary determination of the extent to which the reliability of this 1.3-μπι laser satisfies the stringent require ments of the submarine cable system. The program concentrates on the projection of 1.3-^m laser performance to 10°C, which is the system operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We first discuss the strongly index-guided lasers. Over the last few years, we have fabricated the Channeled Substrate Buried Heterostructure (CSBH), 37 the Etched Mesa Buried Heterostructure (EMBH) 38 · 39 and the Double-Channel Planar Buried Heterostructure (DCPBH) 40 lasers (see Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…There are three ways in which such Au fragments could be inimical to laser reliability: (1) Light blockage-in the course of system instal lation, long-term mechanical relaxation, or mechanical vibration tests, fragments within the mesa might move to partially obstruct the optical output. (2) Electrical shorting-the recovery of lasing operation after sudden termination, effected by mechanical removal of Au fragments from the mirror of a laser that exhibited no preceding or subsequent signs of degradation, suggested that the torn metal could externally short the p-n junction.…”
Section: Optical Inspectionmentioning
confidence: 99%